História oral de vida e saúde mental em Pelotas, RS - Munhoz, Tiago Neuenfeld (2012)
During the last decades, the mental health field has been going through important theoretical, technical and legal modifications, impacting on healthcare users. Thus, this study intends to understand and analyze, through the Oral History methodology, how these alterations affect the routines of two users of Centers of Psychosocial Care (CAPS). It also has the objective of understanding life experiences related to psychological distress. Life stories were analyzed in accordance with structural categories, based on their narratives. The psychological or physical abuses these women underwent at some point in the lives are important factors in relation to their present state of mental health. These oral histories reveal similar problems to those found in other studies with mental health healthcare users in Brazil. According to the narratives, the CAPS s play an important therapeutic role, however, public policies in the sector still don t make up to deficits related to low educational and socioeconomic levels of many users, as well as to their inclusion in the labor market. Further studies addressing gender and mental health could provide important information for the comprehension of these gaps